Multi-level governance as a tool for territorial integration in Europe: Example of the Orient/East-Med Corridor - Ana Perić (Spatial and transport infrastructure development in Europe: Example of the Orient/East-Med Corridor, 2019)
The initiatives related to the Pan-European, later TEN-T, and, finally, Core Network Corridors, are considered the first instrument for territorial cohesion in Europe - even before spatial development policies. Therefore, their significance in connecting various territories across Europe is indisputable. However, putting aside the material benefits, true European integration is not possible without efficient cooperation and coordination. This is particularly true for territories with various past histories, identities and planning cultures: the Orient/East-Med Corridor is a distinctive example of such differences. After presenting the two main principles of territorial integration in Europe - supranationalism and intergovernmentalism, as well as their limitations, the concept of multi-level governance is elucidated. Multi-level governance, i. e. a simultaneous activation of both governmental and non-governmental actors at various jurisdictional levels, comprises two ideal types of institutions: general-purpose political institutions and single-purpose functional jurisdictions. Transnational territories are certainly affected by both types and thus the main question relates to the dynamics and mobilization of institutional and non-institutional actors, rather than revolving solely around strong hierarchy (e. g. between the administrative levels of nation states) or overlapping sectoral/functional entities (in certain domains at the transnational level). However, various types of cooperation are suitable for various administrative and territorial levels. Therefore, the central part of this paper shows forms of intersectoral and interdisciplinary cooperation, particularly elucidating the role of the following levels: transnational, cross-border and local. This is done by clarifying the main principles of multi-level governance relevant for different levels, illustrated with examples of various cooperation forms perceived along the Orient/East-Med Corridor. The paper concludes that only a more intensive interaction among various disciplines and sectors can contribute to the sustainability of transport practices, enhancing territorial cohesion at the same time. – – Die Initiativen im Zusammenhang mit den paneuropäischen, später TEN-T und schließlich den Kernnetzkorridoren gelten als wesentliche Instrumente für den territorialen Zusammenhalt in Europa - noch vor der Raumentwicklungspolitik. Ihre Bedeutung für die länderübergreifenden Verbindungen in Europa sind unumstritten. Wenn man die grundsätzlichen materiellen Vorteile außer Acht lässt, ist eine echte europäische Integration ohne eine effiziente Zusammenarbeit und Koordination nicht möglich. Dies gilt insbesondere für Gebiete mit unterschiedlicher Geschichte, verschiedenen Identitäten und Planungskulturen: Der Orient/East-Med Corridor ist ein markantes Beispiel hierfür. Nach der Vorstellung der beiden wichtigsten Prinzipien der territorialen Integration in Europa - Supranationalismus und Zwischenstaatlichkeit - sowie ihrer Grenzen wird das Konzept der Multi-Level-Governance erläutert. Multi-Level-Governance, d. h. die gleichzeitige Beteiligung von staatlichen und nichtstaatlichen Akteuren auf verschiedenen Zuständigkeitsebenen, umfasst zwei ideale Arten von Institutionen: allgemeine politische Institutionen und funktionale themenbezogene Zuständigkeiten. Transnationale Gebietskörperschaften sind sicherlich von beiden Typen betroffen und so bezieht sich die Hauptfrage auf die Dynamik und Mobilisierung institutioneller und nicht-institutioneller Akteure, anstatt sich ausschließlich um eine starke Hierarchie (z. B. zwischen den Verwaltungsebenen von Nationalstaaten) oder überlappende sektorale/ funktionale Einheiten (in bestimmten Bereichen auf der transnationalen Ebene) zu drehen. Verschiedene Formen der Zusammenarbeit eignen sich jedoch für verschiedene Verwaltungs- und Gebietsebenen. Daher fokussiert dieser Beitrag auf Formen der sektorübergreifenden und interdisziplinären Zusammenarbeit, insbesondere auf die Rollen der transnationalen, grenzüberschreitenden und lokalen Ebenen. Hierzu werden die Grundprinzipien der Multi-Level-Governance ins Zentrum gerückt, die für die verschiedenen Ebenen relevant sind und durch Beispiele für verschiedene Kooperationsformen hinterlegt werden, die entlang des Orient/East-Med Corridors ersichtlich werden. Der Beitrag kommt zu dem Schluss, dass nur eine intensivere Interaktion zwischen verschiedenen Disziplinen und Sektoren zu nachhaltigeren Verkehrsstrategien beitragen und gleichzeitig den territorialen Zusammenhalt fördern kann.
urn:nbn:de:0156-0952043; hdl:10419/213084; https://econpapers.repec.org/RePEc:zbw:arlfob:12
Keywords: 710; territorial integration; transboundary cooperation; multi-level governance; intersectoraland interdisciplinary cooperation; Orient/East-Med Corridor; Territoriale Integration; grenzüberschreitende Zusammenarbeit; intersektorale und interdisziplinäre Zusammenarbeit